Selective inhibition of mTORC1/2 or PI3K/mTORC1/2 signaling does not prevent or modify epilepsy in the intrahippocampal kainate mouse model. (1st January 2020) - Gericke, Birthe; Brandt, Claudia; Theilmann, Wiebke; Welzel, Lisa; Schidlitzki, Alina; Twele, Friederike; Kaczmarek, Edith; Anjum, Muneeb; Hillmann, Petra; Löscher, Wolfgang
Abstract: Dysregulation of the PI3K/Akt/mTOR pathway has been implicated in several brain disorders, including epilepsy. Rapamycin and similar compounds inhibit mTOR. complex 1 and have been reported to decrease seizures, delay seizure development, or prevent epileptogenesis in different animal models of genetic or acquired epilepsies. However, data for acquired epilepsy are inconsistent, which, at least in part, may be due to the poor brain penetration and long brain persistence of rapamycin and the fact that it blocks only one of the two cellular mTOR complexes. Here we examined the antiepileptogenic or disease-modifying effects of two novel, brain-permeable and well tolerated 1, 3, 5-triazine derivatives, the ATP-competitive mTORC1/2 inhibitor PQR620 and the dual pan-PI3K/mTORC1/2 inhibitor PQR530 in the intrahippocampal kainate mouse model, in which spontaneous seizures develop after status epilepticus (SE). Following kainate injection, the two compounds were administered over 2 weeks at doses previously been shown to block mTORC1/2 or PI3K/mTORC1/2 in the mouse brain. When spontaneous seizures were recorded by continuous (24/7) video-EEG recording starting 6 weeks after termination of treatment, no effects on incidence or frequency of seizures were observed. Drug treatment suppressed the epilepsy-induced activation of the PI3K/Akt/mTOR pathway in the hippocampus, but granule cell dispersion in the dentate gyrus was not prevented. When epilepsy-associated behavioral alterations were determined 12–14 weeks after kainate, mice pretreated with PQR620 or PQR530 exhibited reduced anxiety-related behavior in the light-dark box, indicating a disease-modifying effect. Overall, the data indicate that mTORC1/C2 or PI3K/mTORC1/C2 inhibition may not be an antiepileptogenic strategy for SE-induced epilepsy. Highlights: The mTOR signaling pathway has emerged as a therapeutic target for epilepsy. Increased mTOR activity seems to be involved in epileptogenesis in genetic and acquired epilepsies. Here we used two novel brain-penetrant inhibitors to inhibit mTOR activation. This did not prevent or modify epilepsy in the intrahippocampal kainate mouse model. However, a disease modifying effect on comorbid anxiety was observed.